Nanostructured lipid carrier loaded with zingiber officinale and zingiber zerumbet oil for induction of lipolysis in subcutaneous skin layer - Nur Ayshah Rosli, 1988-, author 625762; Azila Abdul Aziz supervisor 509000; Rosnani Hasham @ Hisam, 1977- supervisor 638167; Fakulti Kejuruteraan. Sekolah Kejuruteraan Kimia dan Kejuruteraan Tenaga 619081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Ph.D (Kimia - Bioproses)) - Universiti Teknologi Malaysia, 2019